Application of polydopamine-based materials for advanced techniques in water and wastewater treatment - Arezo Savari; Bawar Shamsaldeen Tahir; Ahmed Mohammed Ahmed; Rauf Foroutan; Bahman Ramavandi (Results in Chemistry)
Polydopamine (PDA), a biomaterial derived from the adhesive properties of marine mussels, has emerged as a multifunctional material for water and wastewater treatment. This review systematically examines recent progress in applying PDA-based materials for removing contaminants, including heavy metals, organic dyes, and pharmaceuticals, from industrial wastewater. The study focuses on the integration of PDA in three main approaches: adsorption, advanced oxidation processes, and membrane separation techniques. Findings indicate that PDA-modified adsorbents achieve high removal efficiencies, with some systems, such as Biosilica-PDA-triethylenetetramine (TEPA), maintaining up to 88 % dye removal efficiency even after ten reuse cycles. Meanwhile, PDA-coated membranes exhibit a significant enhancement in pollutant removal, exemplified by an improvement from 63.5 % to 88.5 % in polyvinylidene fluoride/zinc oxide (PVDF/ZnO) membranes. Furthermore, PDA's capability to introduce numerous active sites through catechol and amine functional groups enhances key interaction mechanisms, including hydrogen bonding and π-π stacking, thereby improving overall pollutant uptake. This review concludes that PDA-based materials present a promising, eco-friendly, and sustainable solution for advancing water treatment technologies, offering advantages such as high stability, reusability, and the potential to significantly reduce environmental contamination.